PENINGKATAN PEMAHAMAN KONSEP SISWA SEKOLAH DASAR MELALUI MEDIA PEMBELAJARAN MATEMATIKA - Razalna Rahmah; Nazahelmalia Putri; Lumatun Nuril Hidayah; Dian Mustika Anggraini (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
This research aims to deeply examine the role and effectiveness of various types of learning media in improving elementary school students' understanding of mathematical concepts. The primary problem underlying this study is the gap between the abstract nature of mathematical objects and the cognitive development stage of elementary students, who are still in the concrete operational phase, leading to poor conceptual understanding. The research method employed is a qualitative approach with a library research design, involving a systematic analysis of 10 relevant scientific literatures. The results indicate that utilizing diverse learning media, including concrete props, visual media, and integrated audio-visual technology, effectively serves as a cognitive bridge for students. These media reduce material abstraction into tangible representations that are easily manipulated, thereby significantly enhancing cognitive learning outcomes, motivation, and active participation in class. A logical consequence of these findings is the necessity for teacher creativity in integrating innovative media to strengthen students' cognitive foundations in mathematics learning.